The influence of profitability, leverage, capital intensity, and firm size on tax aggressiveness during covid-19 pandemic - Berlian Kelline; Einde Evana; Niken Kusumawardani (Asian Journal of Economics and Business Management, 2022)
In Indonesia, businesses have recently engaged in tax aggressiveness. The Republic of Indonesia's Ministry of Finance estimates that by the middle of 2020, tax evasion by businesses as reported by the Tax Justice Network might result in a loss of roughly Rp 68.7 trillion annually in worldwide tax collections. State tax income is reduced as a result of this. Additionally, the Covid-19 pandemic has increased economic instability. The purpose of this study is to investigate the impact of profitability, leverage, capital intensity, and business size on tax aggressiveness during Covid-19 pandemic. Profitability, leverage, capital intensity, and company size are the independent variables in this study, while firm age is the control variable. The dependent variable is tax aggressiveness, which is determined by the effective tax rates (ETR). In the 2020–2021 timeframe, 170 manufacturing companies listed on the Indonesia Stock Exchange were chosen as the target of observation. Using the purposive sampling method, a sample of 100 manufacturing businesses was obtained based on predetermined criteria. The findings revealed that profitability, leverage, and capital intensity all had a considerable impact on tax aggressiveness. While the size of the business has no substantial impact on tax aggressiveness. Age of the firm, which serves as the control variable, has a negative and considerable impact on tax aggressiveness.